Pengaruh Pelaksanaan Anggaran dan Kualitas Sumber Daya Manusia Terhadap Kinerja Manajerial Melalui Penyerapan Anggaran - Nuryenda Pinta Tarigan; Eka Nurmala Sari; Widia Astuty (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
The purpose of this study was to examine and analyze the effect of budget execution and the quality of human resources on managerial performance through direct and indirect budget absorption. The approach used in this research is an explanatory approach. The population in this study were all parts of the Balai Bersar Gunung Lauser National Park. The sample in this study was taken 2 people from Balai Bersar Gunung Lauser National Park consisting of the head of the section and staff so that the number of respondents was 88 people. Data collection techniques in this study used documentation studies, and questionnaires. The data analysis technique in this study used a quantitative approach using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study using the PLS (Partial Least Square) software program. The results of this study prove that 1) budget implementation affects managerial performance, 2) human resource quality affects managerial performance 3) budget absorption affects managerial performance 4) budget implementation affects budget absorption, 5) the quality of human resources affects absorption budget, 6) budget absorption is able to mediate the effect of budget implementation on managerial performance, 7) budget absorption is not able to mediate the influence of the quality of human resources on managerial performance at Balai Bersar Gunung Lauser National Park.